(3GdOQ GdeWdhH aj SQ GdZGdH hGdeZdhH (B( (3aj GdJfLje (B)s - (3jhSa Hf bQbeGS Hf YHO Gddg GdMeRGhj GdMfaj, GejQ GdMGL GdMdHjs
(3ChdgG (B:s
(3GdMeO ddg hGdgfG , hCfJ fhQ GdCfhGQ hHYO deG QCjJ Cgd ReGffG jHMKhf Yf CSQGQ GdZGdH ef Gdedhc ahVYJ dge gPG GdcJGH dSWhQ OjHGLJg Ydi hGVYg eJhLI ChGFd SWhQgG s
(3BNQgG (B:s
(3adjcf eG ChQOfGg Ydi PcQ efc , hGddg jbhd GdMb , hgh jgOi GdSHjd , hSdGe Ydi GdeQSdjf , hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3HgG fXGe GdJYbjHIs
(3cJHJ Yf fSNI HNW GdeDdas
(3HChd GdeLehYI Jedc HGSe CMeO Hf CMeO Hf JeQJGT GdMfai SfI (B904(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs